METHODOLOGY FOR IMPROVING DIDACTIC SUPPORT OF LABORATORY WORKSHOPS BASED ON THE USE OF DIGITAL EDUCATIONAL TOOLS - Tursinboyeva Khalima Otabekovna (Modern American Journals, 2025)
This article discusses the current state of didactic support in physiology laboratory classes in pedagogical higher education institutions, the extent to which new educational resources being created in the formation of this didactic support can help increase students' knowledge, and the extent to which the use of digital educational tools can help increase the effectiveness of laboratory classes.
Keywords: Digital education, laboratory, physiology, biology, virtual laboratory, active, passive.